Pengaruh Citra Perusahaan dan Kualitas Layanan Terhadap Loyalitas dengan Kepuasan Sebagai Mediasi Pada Pelanggan PT Indonesia Comnets Plus Regional Jawa Bagian Tengah - Maria E Deviana; Endang Tjahjaningsih (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract The purpose of this research aims to determine the extent to which the influence of brand image and service quality on loyalty with satisfaction as a mediation toward customers at PT Indonesia Comnets Plus Regional Jawa Bagian Tengah. The population of this research are customers at PT Indonesia Comnets Plus Regional Jawa Bagian Tengah, who have been subscribed from 6 months to more than 5 years.. By using purposive sampling technique, 100 customers were participated as respondents. Based on the reseach, the results declares : 1) Brand Image has positive and significant effect on Satisfaction, 2) Service Quality has positive and significant effect on Satisfaction, 3) Brand Image has no effect on Loyalty, 4) Service Quality has positive and significant effect on Loyalty, 5) Satisfaction has positive and significant effect on Loyalty, 6) Satisfaction mediates the effect of Brand Image on Loyalty, 7) Satisfaction mediates the effect of Service Quality on Loyalty. Keywords : Brand Image, Service Quality, Satisfaction, Loyalty